The effectiveness of EM4 and Acetic Acid activator addition in processing aquaculture waste into liquid fertilizer for the growth of Azolla microphylla biomass - Pintami '; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Aquaculture waste rich in organic materials and it is potencial as basic materials for liquid fertilizer. To increase the N, P and K content, addition of EM4 and acetic acid activators are needed. To understand the effectiveness of the activators in increasing the N, P and K content, a study has been conducted from March to April 2015. There were 5 treatments applied, there was 10 L of pure waste (Po/ control) and 10 L waste that were added with 100 ml EM4 + 1 kg rice bran + 100 gr sugar(P1); 350 ml acetic acid 95% +1 kg rice bran + 100 gr sugar (P2); 100 ml EM4 (P3) and 350 ml acetic acid 95% (P4). Samples were fermented for 12 days. Results shown that the highest N (12,718.34 mg/L) was in the P3, the highest P (70.14 mg/L) was in the P1 and the highest K (11.49 mg/l) was in the P4. The values of organic materials content in the fertilizer produced in this research, however, was lower than that of the standard values mentioned in the SNI No.70/Permentan/SR 140/2011 and thus indicates that the activator is not significantly increase the organic materials in the aquaculture waste.Keyword: aquaculture waste, Liquid Fertilizer, EM4, acetic acid